Economic and environmental impact of pipeline vandalism in the Niger Delta Region - Tukur, Ahmed Umar (2017)
The study investigates the factors that causes and influences crude oil pipeline vandalism in the Niger Delta region of Nigeria. It assess the impact of crude oil spill on the socioeconomic life of the people in the region, it’s economic and environmental impacts. The study was able to achieve its three important specific objectives; to assess the factors that encourage oil pipeline vandalism in the Niger delta region; to design a compensation package most desirable for the Niger Militants and to aggregate the cost of oil pipeline vandalism in the Niger delta region. Both the EFA and CFA were employed in the analysis. The study also developed a compensation model for the militants using choice modeling. Finally the total cost of oil spill losses due to pipeline vandalism were also aggregated. To carry out the study, 269 respondents were selected comprising both militants and some stakeholders in the affected communities from the region for SEM analysis. Also, 300 respondents were selected for the choice models analysis. Both purposive and simple random sampling techniques were used in the selection process. For the first objective of the study, SEM was used and the results from the analysis indicates a significant relationship between poor governance, environmental degradation, poor management, weak legal factors having a significant relationship with crude oil pipeline vandalism and a significant but negative relationship with marginalization. For the second objective, CE was used, the results show the willingness to accept of the militants for a new improved compensation plan with less training allowance. For the third objective, it's revealed that, there is a high cost associated with oil pipeline vandalism, however, the cost can be reduced if the new package is adopted by the government. There is a significant relationship between reduction in land & water pollution intensity, improvement in infrastructural facilities provision and willingness to accept for lower training allowance by militants. There is significant cost associated with oil pipeline vandalism in the region. The following recommendations were offered: Structural improvement in the institutions of governance will be accompanied by a reduction in militancy in the Niger Delta region; a better compensation package accompanied by will to effective implementation can significantly reduce the activities of militancy, hence reduction in pipeline vandalism and oil spill and environmental degradation; The high cost associated with vandalism can be reduced to its minimum level if accompanied by effective public policy implementation.